High completion of Isoniazid Preventive Therapy among HIV-infected children and adults in Kinshasa, Democratic Republic of Congo - YOTEBIENG, Marcel (AIDS, 2015)
We assessed isoniazid preventive therapy (IPT) completion and predictors among HIV-infected children and adults in two HIV clinics in Kinshasa, Democratic Republic of Congo. Between September 1, 2012 and June 15, 2013, 546 children (1–15 years) and 1532 adults (> 15 years) were initiated on IPT; 86.6% (408/470) of children and 88.2% (1129/1280) of adults with an IPT outcome completed their therapy. Patients on ART at IPT initiation were more likely to complete IPT.